Survival outcomes of a population-based cohort of adolescent and young adult (AYA), acute lymphoblastic leukemia (ALL) patients in Ontario, Canada: The IMPACT Cohort. (2018) - Lau, Cindy; Pole, Jason; Sutradhar, Rinku; Baxter, Nancy; Nathan, Paul; Gupta, Sumit
No abstract available